Optimizing Knowledge Management Practices for Intellectual Capital Development at Universitas Islam Nusantara - Sukandar, Ahmad; Hamdan Fathurrohman; Guntur Rijaluddin (International Journal of Nusantara Islam, 2024)
This study aims to evaluate knowledge management practices in an Islam-based higher education environment, focusing on the utilisation of intellectual capital at Universitas Islam Nusantara Bandung. In the context of the digital era and global competition, higher education institutions’ ability to manage knowledge effectively is a key factor in improving academic quality and institutional competitiveness. This research uses a qualitative approach with a case study method, and data collection techniques through in-depth interviews, participatory observation, and institutional documentation. The results showed that knowledge management practices at Uninus covered the processes of knowledge identification, creation, dissemination, and implementation, although the implementation is still partial and conventional. The strategies implemented include the documentation of explicit knowledge and the capacity building of human resources in managing tacit knowledge. The conversion of tacit knowledge into explicit form is done through scientific forums and expertise-based assignments, but is not yet fully structured. Evaluation of the supporting tools indicates that some elements, such as document management, digital portals, expertise taxonomy, and ICT infrastructure, are available but not yet optimally integrated. These findings suggest that the effectiveness of knowledge management is highly dependent on the synergy between institutional strategy, technological readiness and organizational culture. Thus, this study suggests the importance of a holistic approach and strengthening institutional policies to maximise the potential of knowledge management in developing intellectual capital in Islamic higher education.